Keanekaragaman Jenis Vegetasi di Kawasan Resort Kembang Kuning Kabupaten Lombok Timur - Sumarjan, Sumarjan (Biocaster : Jurnal Kajian Biologi, 2021)
The purpose of this study was to determine the diversity of vegetation types in the Kembang Kuning Resort Area, Jeruk Manis Village, Sikur District, East Lombok Regency, based on the density of vegetation types. The type of research used is descriptive quantitative. The population in this study were all plant species in the Kembang Kuning Resort Area. Purposive sampling method was used to determine the location and grouping based on growth criteria to obtain data on species richness. A total of 3 research plot locations were determined, namely: plot A (top), plot B (middle), and plot C (bottom). The analysis was carried out descriptively quantitatively based on the Shannon-Wiener (H') species diversity index. The results obtained for plot A area are 19 species with an H' value of 1.117 in the medium category, for plot B area there are 17 species with an H' value of 2.001 in the medium category, and for plot C area 16 species are found with an H' value of 7,045 in the high category. The conclusions obtained are the tree-level diversity index in all areas of plot A, plot B, and plot C of 3.38 in the high category.